Nurses' Experiences of Establishing Meaningful and Effective Relationships With American Indian Patients in the Cancer Care Setting - Natalie M. Pool PhD, RN (SAGE Publishing, 2019)
Introduction The establishment of caring relationships with racial and ethnic minority populations is challenging for many cancer care nurses. Nurses serving American Indian (AI) patients frequently encounter population-specific issues, yet their experiences are largely unknown. Objective The purpose of this study was to describe the meaning of the AI patient-cancer care nurse relationship from nurses' perspectives. The study included three objectives: (a) to describe the immediate experiences of nurses that have engaged in cancer care relationships with AI patients, (b) to identify the underlying structures of the AI patient-cancer care nurse relationship as described by nurses, and (c) to interpret the meaning of the patient-nurse relationship within the context of AI cancer care experiences. Methods This was an interpretive phenomenological study using a hermeneutical process for data collection and analysis of multiple, exploratory interviews. Thematic reduction was completed to explicate the fundamental structures of this particular relationship. Reduction of individually situated themes resulted in seven shared meta-themes including from task to connection; unnerving messaging; we are one; the freedom of unconditional acceptance; attuning and opening; atoning for the past, one moment at a time; and humanizing the inhumane. Results Nine cancer care nurses participated. Reconstitution of data and reflective writing suggested that the essential meaning of the AI patient-cancer care nurse relationship was expressed in contradictory yet simultaneous patterns for nurses. Nurses sought synchronicity with their AI patients despite their contextual differences and similarities, yet most lacked adequate cultural safety training. Being in relationship provided nurses great purpose within the universal human context of caring. Conclusions Results contribute to the development of interventions designed to improve both the AI cancer care experience and the support and training of nurses. The mutually dependent nature of the patient-nurse relationship implies that strengthening and improving support for one entity may in turn positively impact the other.